Sustained Attention in Children with Primary Language Impairment: A Meta-Analysis - Ebert, Kerry Danahy (2011)
PURPOSE: This study provides a meta-analysis of the difference between children with primary or specific language impairment (LI) and their typically developing peers on tasks of sustained attention. The meta-analysis seeks to determine if children with LI demonstrate subclinical deficits in sustained attention and, if so, under what conditions. METHODS: Articles that reported empirical data from the performance of children with LI, in comparison to typically developing peers, on a task assessing sustained attention were considered for inclusion. Twenty-eight effect sizes were included in the meta-analysis. Two moderator analyses addressed the effects of stimulus modality and ADHD exclusion. In addition, reaction time outcomes and the effects of task variables were summarized qualitatively. RESULTS: The meta-analysis supports the existence of sustained attention deficits in children with LI in both auditory and visual modalities, as demonstrated by reduced accuracy compared to typically developing peers. Larger effect sizes are found in tasks that use auditory and linguistic stimuli than in studies that use visual stimuli. CONCLUSIONS: Future research should consider the role that sustained attention weaknesses play in LI, as well as the implications for clinical and research assessment tasks. Methodological recommendations are summarized.